ROLE OF COMMUNITY LEARNING CENTER (CLC) “HANDAYANI” BATIK TRAINING PROGRAM IN ERADICATE EXTREME PROVERTY - Lutfi Ariefianto (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
This study aims to determine the role of learning centers in tackling poverty. In this study, using a case study with a qualitative approach, while data analysis using a model of Miles and Huberman namely data collection, data reduction, data presentation, and conclusions. While data collection techniques using the technique of interview, observation and documentation. The results of this study indicate that the role of CLC has a role that is empowering communities and improving the quality of life, the role of a direct impact on poverty reduction as well as social protection, are creating business opportunities, and improve human resources. The conclusion of this study is the role of learning centers Handayani has the role of empowering the community, while improving the quality of life of citizens of learning that has followed the program batik was able to understand and apply the theory learned after the program batik implemented, and is not uncommon in the learners are able to produce batik itself. Besides the effort to reduce poverty CLC Handayani have a strategy in tackling social protection is one of them. This strategy is to improve their economy after the program learn batik, while creating business opportunities and women devoted to the participants who previously did not have a job then given the batik program. While on peningktan human resources granted in order to improve the competence of work and improve the skills they have. Suggestions for CLC Handayani more direct citizen should learn separately present at the time the program is in progress, and not just present only at the time of the competency test in order to develop learning outcomes.